STRATEGY OF MADRASAH PRINCIPALS IN IMPROVING STUDENTS' DISCIPLINE (Case study of Nurul Jadid Islamic Senior High School) - Kurniyawan, Hendi; Sain, Zohaib Hassan; hefniy, hefniy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses the strategies implemented by the principal to improve student discipline at Madrasah Aliyah Nurul Jadid (MANJ), Probolinggo Regency, East Java Province. Using a qualitative approach, this study explores various strategies based on the leadership principles of the Prophet Muhammad SAW, personal approach, socialization of rules, appreciation for disciplined students, and parental involvement. The research findings indicate that these strategies, such as attendance before learning, monitoring student attendance, and consistent application of sanctions, have succeeded in creating a strong and sustainable culture of discipline in schools. However, challenges that arise related to parental intervention require a more proactive approach, such as through open communication and discussion forums. Although there is no quantitative data to support the claim of a decrease in student violations, this provides a positive indication of the effectiveness of the strategies implemented. Therefore, ongoing efforts to improve student discipline need to be carried out through periodic evaluation and adjustment of strategies according to future needs, in order to create an educational environment that is disciplined, productive, and supports the holistic development of students.